Perbandingan Efektivitas Metode EOQ dan JIT dalam Pengelolaan Persediaan pada PT XYZ - Esha Putri Meilani; Fahriza Nurul Azizah (Universitas Indraprasta PGRI Jakarta, 2023)
PT. XYZ is a manufacturing company engaged in bodywork sector. Every company surely expects high profit. One of the ways to achieve the goal is by minimizing the expenses. Economic Order Quantity (EOQ) and Just In Time (JIT) methods are commonly used methods to save inventory costs. This study aims to compare which method is more effective and efficient in reducing inventory costs at the company. The results of the study show that the JIT method can reduce inventory costs by 91.14% for plate with 2mm 4x8 standard and 93.62% for plate with 3mm 4x8 standard, while the EOQ method can reduce inventory costs by 33.45% for both types of the raw materials. Based on the results above, it can be concluded that JIT method is more effective than EOQ method in reducing inventory costs in the company.